Who needs experts most? B oard industry expertise and strategic change—a contingency perspective - Oehmichen, Jana; Schrapp, Sebastian; Wolff, Michael (Strategic Management Journal, 2017)
Research summary: We analyze the effects of board industry expertise on corporate strategic change and the moderating role of institutional quality. We suggest that country‐level contingency factors mitigate the effect of experienced boards on strategy formation by providing alternative sources of information and control in strategic matters. We develop institutional quality as institutional information provision and institutional control provision to test our hypotheses on a sample of firms from MSCI E urope and the S&P 500. Our findings confirm that industry expertise is a salient driver of strategic change across countries. The strength of the effect, however, depends on the institutional quality. We submit that weak institutions require greater board industry expertise as an alternative channel of information and control . Management summary: This study provides new empirical evidence that experience in the firms' industries enables directors to increase strategic change. Our findings show that this effect is even stronger in countries with weak regulatory environments. We hereby provide guidance for multiple stakeholders. First, shareholders seeking a more active adjustment of their firms' strategies may want to compose boards that leverage such experienced directors. Second, directors can use their industry experience to control and to challenge managers better to move beyond the status quo. Third, managers lacking access to information on potential strategic change can use such experienced directors for strategic advice and as a source of information. Overall, we add to the understanding of the corporate board's role in shaping strategy and the influence of weak regulations . Copyright © 2016 John Wiley & Sons, Ltd.